ROLE PLAY AS A TECHNIQUE OF DEVELOPING LEARNERS' PROFESSIONALLY SIGNIFICANT COMPETENCES - Ivanova, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article addresses essential aspects of role play as a technique aimed at facilitating military students' professionally significant competences. The study undertaken here advocates the task-based language teaching as an integral part of the military students’ vocational training at the law faculty. Hence the goal of our study is to provide theoretical justification and methodological development of the concept of role play in foreign language teaching as a means of promoting second language learning and facilitating vocational training. We have analysed the impact of role play on the learner acquisition processes and forming of their professionally significant competences. We have identified stages and algorithms of role play, examined its components and characteristics in foreign language teaching. The conceptual framework of the study follows the model of professional competence approach. Research and experience data obtained in our experimental work make it possible to identify the significance of role play in second language learning designed for military students’ professional development in educational programs at law faculties.